DEVELOPMENT OF LOW-COST CLINICAL BLOOD PRESSURE DATA RECORDING UNIT WITH HIGH SAMPLING RATE - Ega, Adindra Vickar; Ginanjar, Gigin; Tantokusumo, Timotius Christopher (Instrumentasi, 2023)
This paper discusses the improvement of blood pressure recording unit in sampling rate and cost efficiency from the previous recorder using Arduino and PLX-DAQ. In order to increase the sampling rate, the NI-myDAQ device and LabVIEW program were used. The recording unit was able to record the blood pressure samples with the sampling rate 200000 samples/second which complies with the ISO/TS 81060-5 : 2019 with relatively low-cost. However, further development in recording Korotkoff sounds, determining systolic, diastolic, and mean arterial blood pressures are required.Keywords: blood pressure, recording unit, ISO/TS 81060-5, sampling rate, low-cost